Effects of Sleep Fragmentation and Induced Mood on Pain Tolerance and Pain Sensitivity in Young Healthy Adults - Rosseland, Ragna; Pallesen, Ståle; Nordhus, Inger Hilde; Matre, Dagfinn; Blågestad, Tone (Frontiers in Psychology, 2018)
Background: Experimental research exploring the sleep/pain-relationship has typically focused on total or partial sleep deprivation, hereby failing to reproduce the mere fragmented sleep pattern typically observed in patients with chronic pain. Further, little research is done on how affect moderates the sleep–pain relationship after sleep fragmentation. The present study sought to clarify the relationship between pain, sleep and positive and negative affect. Methods: In an experimental counterbalanced crossover design, 35 healthy young adults were subjected to several pain measures after one night of fragmented sleep, compared to one control night of normal sleep, both conducted in their own homes, and respectively, positive and negative affect induction using validated film clips and facial feedback procedures. Sleep was monitored using sleep diaries. Results: Increased pain sensitivity after one night of experimentally induced sleep fragmentation was found, compared to after one control night of undisturbed sleep. No main effects of induced affect on pain were found, and sleep x induced affect interaction was not significant. Conclusion: The present study supports the adverse effect of sleep fragmentation on pain sensitivity, however, affect was not found to be a moderator in the sleep–pain relationship. The results underline the need for further research within this field.